Ekstrak Etanol Daun Kacang Panjang (Vigna unguiculata (L.) Walp): Kajian Morfometri Insula Pankreatika Model Tikus Diabetes: Ethanol Extract of Some Cowpea (Vigna unguiculata (L.) Walp) Leaves: Morphometry Study of Pancreatic Islet of Diabetic Rat Model - Solehah, Puput Octaviani; Tarusu, Fikhta Agnesya; Tandi, Joni; Dewi, Niluh Puspita; Ratih Lintin, Gabriella Bamba; Fitriana, Yuli; Pakaya, David (Universitas Tadulako, 2019)
Diabetes is characterized by an increasing of blood levels and progressive changes in the structure of pancreatic islet of pancreas. Natural ingredients that contain antioxidants such as some cowpea leaves can be an alternative treatment for diabetes. This study aims to examine the effect of ethanol extract of some cowepea leaves (Vigna unguiculata (L.) Walp) on morphometry (perimeter and diameter) of pancreatic islet of diabetic rat models. The type of research is quasi-experimental with posttest group design. Samples were 30 male wistar rats, age 8 weeks, BW 250-300 grams, that induced by single dose of STZ 40 mg/kg BW. Rats were divided into 5 groups. Group A: normal control, Group B: negative control, Group C: positive control, Group D: DM rats with 100mg/Kg BW extract therapy, Group E: DM rats with 200mg/Kg BW extract therapy, Group F: DM rats with extract therapy 300mg/Kg BW. Blood sugar levels were measured on days 7, 14 and 21. Pancreatic tissue was prepared with 5Î¼m thickness and stained with Hematoxylin Eosin. The sample was observed under 400x magnification microscope. The observation uses Image J software to measure the perimeter and diameter of the pancreatic insula. Data were analyzed by non-parametric Kruskal Wallis and post hoct Mann Whitney statistical tests. Blood glucose level was obtained on 21st day with the highest mean in group B (246.8Â±156.3) and lowest in group A (67.2 Â±7.85), perimeter of pancreatic islet was significantly different (p=0.026), the diameter is significantly different (p =0.046). Ethanol extract of some cowpea (Vigna unguiculata (L.) Walp) leaves with dose of 300mg/kgBB helps to restore the blood and morphometry of pancreatic islet model of diabetic rats.